Tradisi Magoak-Goakan pada Nyepi Desa Sebagai Potensi Daya Tarik Wisata Spiritual Di Desa Tambakan Kecamatan Kubutambahan Kabupaten Buleleng. - I Ketut Wardana Yasa (UHN IGB Sugriwa Denpasar, 2018)
The tourism development such as beach, mountain, temples, and dance or other tourist attractions are ussual we can see in Bali. But one of the most rare tradition which is carried out by the peoples in Tambakan Village is Megoak Goakan as part of Silent day Ceremony which is held every one year. This tradition was held from Ngurah Panji Sakti Kingdom in Buleleng. Big potenstion to make this tradition as one of the tourist attraction, which can be held everyday. Tambakan Village has a strategic location. It close to Penelokan, one route to sangeh, plaga, Tukad Bangkung, bagus Agro to penelokan. The asumtion that the development of this tradition can increase the social income for the peoples in Tambakan Village in the future.